Acceptability of hygiene, face covering and social distancing interventions to prevent exacerbations in people living with airways diseases. Issue 5 (21st October 2021) - Hurst, John R; Cumella, Andrew; Niklewicz, Camila Nagoda; Philip, Keir E J; Singh, Victoria; Hopkinson, Nicholas S
Abstract : Interventions to prevent the spread of SARS-CoV-2 have been associated with substantial reductions in exacerbations of airways diseases, likely through reduced transmission of other respiratory viruses. We surveyed 4442 people with airways disease (asthma=3627, bronchiectasis=258, chronic obstructive pulmonary disease=557) to gauge attitudes and intentions towards continuing such measures after the COVID-19 pandemic. 47% intended to continue wearing a face mask in indoor public spaces, and 61% thought everyone should be required to do so during the 'influenza season. Women, those with bronchiectasis, and older people were generally more cautious. Respiratory virus infection control measures should be considered in clinical guidelines and public health recommendations.